1990
DOI: 10.1210/jcem-70-3-804
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Leu227by Pro in Thyroxine-Binding Globulin (TBG) Is Associated with Complete TBG Deficiency in Three of Eight Families with This Inherited Defect*

Abstract: The T4-binding globulin (TBG) gene is a single copy located on the X-chromosome. Previous studies have failed to elucidate the molecular defect in individuals with complete TBG deficiency (TBG-CD). Indeed, no major deletions, insertions, or other rearrangements were observed in the TBG gene of six unrelated males with this defect. To clarify the molecular basis of TBG-CD, we have cloned and sequenced the TBG gene of an affected male (CD5) of French Canadian origin. The sequence of the exons encoding the mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 23 publications
2
32
0
3
Order By: Relevance
“…In the absence of clinical evidence of hypo-or hyperthyroidism, they are often uncovered by the fortuitous finding of abnormally high or low concentrations of total T4 in blood (Mori et al 1990). Normal levels of corticotropin-releasing hormone (CRH), and even its increase in response to stress, were observed in null mutants of another hormone-binding protein, namely CRH-binding protein (Karolyi et al 1999).…”
Section: Ttr Null Mutants and Biological Importance Of Redundancymentioning
confidence: 99%
“…In the absence of clinical evidence of hypo-or hyperthyroidism, they are often uncovered by the fortuitous finding of abnormally high or low concentrations of total T4 in blood (Mori et al 1990). Normal levels of corticotropin-releasing hormone (CRH), and even its increase in response to stress, were observed in null mutants of another hormone-binding protein, namely CRH-binding protein (Karolyi et al 1999).…”
Section: Ttr Null Mutants and Biological Importance Of Redundancymentioning
confidence: 99%
“…Blood samples from her children were not analyzed, since we could not obtain any collaboration with them because of their young age. It was concluded that TBG-Kumamoto was a different familial type of TBG deficiency from those reported previously [5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 62%
“…More recently, gene analyses have been performed on families with partial or complete TBG deficiency [5][6][7][8][9][10][11][12]. To our knowledge, there are three different types of complete TBG deficiency in which gene analyses have been undertaken.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like other TBG variants, the mutation found in TBG-PDJ was a nucleotide substitution at codon 363, replacing proline with leucine. It is of interest to note that the replacement of leucine by proline was reported in one family with complete TBG deficiency (TBG-CD5) [17]. Since proline is an aromatic amino acid which is thought to cause a helix breakage, the mutation Pro to Leu or vice versa may influence the tertiary structure of the TBG molecule.…”
Section: Resultsmentioning
confidence: 99%